Seroprevalence of Neutralizing Antibodies against Japanese Encephalitis Virus among Adolescents and Adults in Korea: A Prospective Multicenter Study - Byung Ok Kwak; Young Se Kwon; Young Jin Hong; Chung Hyun Nahm; Woori Jang; Young Uh; Yong Gon Cho; Jimyung Kim; Myungshin Kim; Dong Hyun Kim (Vaccines, 2020)
The immunization schedule for the Japanese encephalitis (JE) vaccine in Korea is a two-dose primary series at 12–24 months of age, followed by booster doses 12 months after the second dose and at the ages of 6 and 12 years. Although the number of JE cases has markedly decreased after the universal vaccination program, JE predominantly occurs in adults. The aim of this study was to assess the age-specific prevalence of the JE-neutralizing antibody (NTAb) among adolescents and adults in Korea. A total of 1603 specimens were collected from a healthy Korean population above 15 years old in five provinces. The JE-NTAb titers were measured with the pseudotyped virus assay and considered to be positive at ≥ 1:50. The seropositivity of JE-NTAb was the highest in the 15–29 years category (>95%) and gradually began to decrease in the age group of 30–44 years (89.42%). The lowest and second lowest JE-NTAb seropositive rates were observed among those aged 70 years or older (59.77%) and those aged 55–59 years (75.24%), respectively. Subjects from Seoul exhibited the highest JE-NTAb titer in all age groups compared to other provinces. In conclusion, the JE-NTAb seropositive rates and titers have maintained appropriate levels in the general Korean population. We propose that adult immunization and boosters at 12 years of age against JE are not strongly recommended in Korea.